Pengaruh Analisis Rasio – Rasio Early Warning System (EWS) Terhadap Harga Saham Pada Perusahaan Asuransi Yang Listing Di Bursa Efek Indonesia (2009- 2012) - Pramono Putro Suwiralim; Haryetti '; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to determine the effect of Liquidity Ratio,Claimexpense Ratio, Agent’s Balance to Surplus Ratio and Ratio of Premium Growth. Firm’s value of this research was measured by Stock’s Price. We use secondary data which get from Indonesian Capital Market Directory (ICMD). Purposive sampling is used to get the sample. Descriptive statistics, multiple linear regression analysis (partially analysis), t-test and F-test are used to analyse the data. The result shows that both Liquidity Ratio and Ratio of Premium Growth were significantly affected Stock Price. Meanwhile, both Claim Ratio and Agent’s Balance to Surplus Ratio had no effect at all on Stock Price.Keywords: Liquidity Ratio (Liabilities To Liquid Assets Ratio / X1), Ratio Claim(Incurred Loss Ratio / X2), Agents' Balance To of Surplus Ratio ( X3),Ratio of Premium Growth ( Premium of Growth Ratio / X4 )